2017
DOI: 10.1016/j.neuroscience.2017.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nkcc1 promotes axonal growth and motor recovery in ischemic rats

Abstract: Bumetanide is a selective inhibitor of the Na-K-Cl-co-transporter 1(NKCC1). We studied whether bumetanide could affect axonal growth and behavioral outcome in stroke rats. Adult male Wistar rats were randomly assigned to four groups: sham-operated rats treated with vehicle or bumetanide, and ischemic rats treated with vehicle or bumetanide. Endothelin-1 was used to induce focal cerebral ischemia. Bumetanide administration (i.c.v.) started on postoperative day 7 and continued for 3 weeks. Biotinylated dextran a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…This is concordance with previous in vivo results showing a reduction in the infarction volume as well as in the ischemic necrotic cell death, especially remarkable when bumetanide was applied preinjury [60,63,67,68]. A recent study has shown that the inhibition of NKCC1 from day 7 post stroke enhanced axonal sprouting from uninjured neurons, resulting in a significant behavioral improvement [66].…”
Section: Cation-chloride Cotransporterssupporting
confidence: 92%
See 2 more Smart Citations
“…This is concordance with previous in vivo results showing a reduction in the infarction volume as well as in the ischemic necrotic cell death, especially remarkable when bumetanide was applied preinjury [60,63,67,68]. A recent study has shown that the inhibition of NKCC1 from day 7 post stroke enhanced axonal sprouting from uninjured neurons, resulting in a significant behavioral improvement [66].…”
Section: Cation-chloride Cotransporterssupporting
confidence: 92%
“…Contrary to what it was seen for NKCC1, the amount of KCC2 at both mRNA and protein levels was downregulated in both rat and mouse models of ischemic stroke [45,64,66,73,74]. Curiously, whereas the KCC2 levels in the plasma membrane are notably reduced 3 h post ischemia [74], there is a progressive decrease in the levels of total KCC2 given that it is significant on days 1 and 7 post stroke, but not at 2 h after injury [64].…”
Section: Cation-chloride Cotransportersmentioning
confidence: 86%
See 1 more Smart Citation
“…In models of neurodegenerative diseases, including 2VO, along with degeneration or elimination of fibres and synaptic contacts reflecting dysfunction [ 31 , 33 , 43 , 50 , 51 ], sprouting and mediator activation (hyperfunction) have been described [ 52 , 53 , 54 , 55 ]. Changes in mChAT and sChAT activity in response to in vivo influences are, as a rule, the equivalent of plastic changes in the cholinergic synaptic pool.…”
Section: Discussionmentioning
confidence: 99%
“…Activated GABA inhibits axonal regeneration by stimulating the Rho/Rock signaling pathway and p75NTR synthesis, increasing cell death [ 83 , 84 ]. It also inhibits GABA stimulation, Rho/Rock signaling and p75NTR levels, reducing cell death, accelerating regeneration and increasing endogenous BDNF levels [ 85 ]. Moreover, co-treatment with dexamethasone, which possesses antiedematous activity, and bumetanide, which blocks the aquaporin 1 receptor and also decreases edema, exerts a synergistic inhibitory effect on the edema that develops after peripheral nerve regeneration and healing [ 86 ].…”
Section: Medicationsmentioning
confidence: 99%